Lymphatic sparing laparoscopic varicocelectomy with or without testicular artery preservation: is there a difference? - Abdelaziz Yehya; Mohamed Abdalrazek; Ibrahim Gamaan; Ahmed Fathy; Wael El Batal (SpringerOpen, 2020)
Abstract Background Lymphatic sparing laparoscopic Palomo varicocelectomy is a safe and reliable technique for varicocele treatment in adolescents and children. The purpose of this study was to compare the outcomes of lymphatic sparing laparoscopic varicocelectomy with and without testicular artery preservation. The prospective random allocation of selected patients was done at Al-Azhar University Hospital, Pediatric Surgery Department from February 2010 till January 2015. All patients underwent lymphatic sparing laparoscopic varicocelectomy and they were divided into two equal groups, group A underwent laparoscopic Palomo without testicular artery sparing and group B underwent the procedure with testicular artery sparing. The main outcome included operative time, postoperative hydrocele, and persistence of varicocele, together with catch-up testicular growth or testicular atrophy. Results One hundred and sixty male patients presented with left-sided primary varicocele that was diagnosed clinically and affirmed by color Doppler ultrasonography. The mean age was 14.25 ± 1.6 years (ranged 13-16 years). There was one case of persistent varicocele in group A, compared to 8 cases in group B with a statistically significant difference (p = 0.016). A significant difference had been found in the operative time (p = 0.001) between both groups. No hydrocele or testicular atrophy had been detected in both groups. No significant inter-group differences were seen in aspects of age, varicocele grade, and catch-up testicular growth. The mean follow-up period was 42 months (24-60 months). Conclusion Lymphatic sparing laparoscopic Palomo varicocelectomy was superior to that with testicular artery preservation as regard varicocele persistence and operative time and hence is preferable for the management of primary pediatric varicocele.